THE EFFECT OF MICROWAVES ON MICROORGANISMS - Valsechi, O.a.; Horii, J.; Angelis, D. De F. De [UNESP] (Instituto Biológico, 2024)
This work is a literature review on the use of microwaves for pasteurization processes and/ or the reduction of the microbiological biota in foods. It presents background as well as latest information on the methodology being used in these processes, putting emphasis on the newest developments of the technology being used today.

Este artigo apresenta uma revisão literária sobre o uso de microondas visando a pasteurização ou a diminuição da microbiota em alimentos, fornecendo informações fundamentais e atuais sobre a metodologia desse tipo de processo, bem como salienta avanços tecnológicos.
O EFEITO DAS MICROONDAS NOS MICRORGANISMOS
Keywords: Microwaves; pasteurization; microorganisms.; Microondas; pasteurização; microrganismo.